The military and law enforcement in peace operations lessons from Bosnia-Herzegovina and Kosovo - Friesendorf, Cornelius (DCAF documents, 2010)
After war, police forces are often unable or unwilling to put pressure on suspected war criminals, organized crime groups, and other spoilers of sustainable peace. This book sheds light on the role of international military forces in post-conflict law enforcement. Drawing on numerous interviews, it shows that EU and NATO military forces have not systematically fought serious crime in Bosnia-Herzegovina and Kosovo. International actors need to better balance their own interests as well as the requirement to separate military and police functions with the urgent need to protect individuals in war-torn countries. The policy recommendations in the book are aimed at contributing to more effective, efficient, and legitimate peace operations in the Balkans and beyond.